Disseminated Intravascular Coagulation Is a Frequent Complication of Systemic Inflammatory Response Syndrome - Gando, Satoshi; Kameue, Takashi; Nanzaki, Satoshi; Nakanishi, Yoshimi (Thrombosis and Haemostasis, 1996)
To evaluate the role of disseminated intravascular coagulation (DIC) and to determine the influence of antithrombin, protein C, and plasminogen activator inhibitor 1 on multiple organ dysfunction syndrome (MODS) and outcome in patients with systemic inflammatory response syndrome (SIRS), we made a prospective cohort study. The study subjects consisted of thirty-five patients who exhibited two or more of the conditions of SIRS for more than three consecutive days. They were classified into subgroups of survivors (n = 13) and nonsurvivors (n = 22). The global coagulation and fibrinolytic markers, antithrombin, protein C, and plasminogen activator inhibitor 1 were measured on the day of the diagnosis of SIRS, and also on the 1st, 3rd, and 5th days. The results of these measurements, demographic data, criteria of severity, incidence of MODS were compared between the subgroups. For prediction of patient’s death, a receiver operating characteristic (ROC) curve analysis was made. DIC was frequently associated with SIRS patients (29/35, 82.9%). A significant decrease in the DIC score was found in the survivors (p = 0.0001). None of them suffered from DIC on the 5th day. In the nonsurvivors, low levels of protein C and antithrombin and markedly high values of plasminogen activator inhibitor 1 continued up to the 5th day, no improvement of the DIC was observed during the study period and the number of the dysfunctioning organs were significantly higher than in the survivors. Plasminogen activator inhibitor 1 on the 5th day had prognostic value for the prediction of death on the SIRS patients. In conclusion, DIC occurs commonly in patients with SIRS and may be the main determinant for the outcome of these patients. Changes in antithrombin, protein C, and plasminogen activator inhibitor 1 are one of the aggravating factors of MODS. Furthermore, plasminogen activator inhibitor 1 is a good predictor of death in these patients.